STUDY AND CHARACTERIZATION GROWTH OF FOUR MICROALGAE SPECIES AND TEST ANTIMICROBIAL ACTIVITY - Salim, Marniati (Jurnal Zarah, 2018)
Abstract In this study to the growth characteristics of microalgae (Dunaliella salina, Nannochloropsis oculata, Tetrasel mis chuii & Chaetoceros calcitrans), in different mediums, namely Boldâs Basal Medium (BBM) and BBM modification of sea water. The results obtained from microalgae (N.oculata, T.chuii, C.calcitrans) are better grown on BBM media while microlaga D.salina grows well on BBM modification of sea water. Microalgae biomass is extracted by maceration method in hexane and methanol solvents. Test bacteria used gram positive (Staphylococcus aureus) and gram negative (Escherichia coli). Inhibitory zone diameter results were compared with antimicrobial sensitivity tests according to Clinical and Laboratory Standards Institute (CLSI). From the results of microalgae hexane and methanol extract antibacterial activity tests (D.salina, N.oculata, T.chuii, C.calcitrans) showed that the extract was not too sensitive to inhibit bacterial growth.   Keywords: microalgae, medium, antimicrobial